Pelatihan Keterampilan Mendongeng untuk Keluarga Nelayan - Tina Afiatin; Budi Andayani (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
Storytelling is an efective way in instilling moral in children and forming character. Storytelling skill is needed by parents, especially in the fsherman families, to improve parenting quality. However, the parents in Tou village have not known and have never gotten the training on good storytelling. Terefore, in the community service activity of the Faculty of Psychology, UGM, it was given storytelling skill training for the fsherman families. Te storytelling skill training was held in Tou village, Moilong, Banggai, Central Sulawesi, belonging to the outermost, the most front and remote region. Te training was attended by 25 people of Tou village. Te training was held for two days with training materials: the lecture of good storytelling technique, the exercise of verbal and non-verbal communication, the practice of storytelling for the participant’s children, and the feedback of practicing storytelling skill. Te training results were analyzed with the qualitative and quantitative approach. Te qualitative analysis results (from observation, interview, and focus group discussion) showed that all participants felt getting new knowledge and skill, that is the useful storytelling skill in parenting. Te quantitative analysis results (parenting scale score) with statistic using t-test, the result was that there was signifcant reduction of dysfunctional parenting (t = -5,87;  p <0,001) between before and afer getting storytelling skill training.